Investigating Implicature and Cooperation Concepts in Selected Quranic Verses from Gender Perspective - Mohammed, Zainab Saad (Al-Adab Journal, 2015)
Implicatures frequently occur in daily conversations, yet their use is often not fully understood. Generally speaking, implicatures are used to hint, suggest, or avoid directness for various reasons. They seem to be in a direct contrast to Grice's (1975) view that utterances need to be informative. Implicatures may purposely cloak direct information, so the hearer would need to infer what the message of the implicature is. Also, they can be used to withhold information or to allude to certain information, particularly in cases when doing the opposite would be indiscrete, impolite, unethical, or threat to somebody's standing. Clearly, a speech situation will have an impact on the choice and frequency of implicatures, so will other important social variables, such as gender. The research aims at finding gender differentiation in the use of implicature, a subject which is rarely studied